A new material supply mechanism for plunger type injection molding - Mohamad Al Rassid, Mohamad Borhanudin (2012)
This project was carried out to develop the new material supply mechanism for plunger type injection molding. The objective of this project is to design a new material supply mechanism that can overcome the limitation on the plunger type injection molding at the same the to improve the function of the current material supply that only act as a material storage. The development process consists of the design process and the validation process. The new design consists of the new function to give more functionality to the current material supply. The new function consists of the mixing mechanism and also the heating element and in additional to that, the valve is also being integrated into the mechanism in order to control the molten plastic from flowing out. The process of selecting a new material supply mechanism are made by selecting the best concept from three concept of a new material supply mechanism using a Pugh concept selection method. Due to the constrain in obtaining the component part, validation process was carried out by using CAE software. The validation process is done by using the CAE software analysis in the temperature flow on the mechanism. The value of the temperature was set to the three variable values to see the different flow of the temperature. Based on the analysis of the temperature flow, it shows that the new material supply mechanism are achieving the objective.